A comparative study of dexmedetomidine versus clonidine in epidural anaesthesia to assess the level of sedation in patients undergoing lower abdominal and lower limb surgery - Pathak, Vinay; Kushwaha, B. B.; Chandra, Girish; Bhatia, V. K.; Gupta, Akash; Kumar, Shubham (International Journal of Research in Medical Sciences, 2018)
Background: To compare study of dexmedetomidine versus clonidine in epidural anesthesia to assess the level of sedation in patients undergoing lower abdominal and lower limb surgery. Methods: This was a comparative study conducted on admitted ASA grade I and II patients undergoing lower abdominal and lower limb surgeries. The patients were divided into three groups of 30 patients each, according to the epidural medication they received:-Group A-received 15ml of bupivacaine (0.5%) and dexmedetomidine (1.0µg/kg body weight) in 1ml of normal saline; Group B-received 15ml of bupivacaine (0.5%) and clonidine (2.0µg/kg body weight) in 1ml of normal saline; Group C-received 15ml of bupivacaine (0.5%) with 1ml of normal saline. The heart rate, blood pressure, sensory dermatome level, Motor blocked level, pain and VAS were recorded at different time intervals. The side effects were also noted. Results: The baseline parameters were comparable among the groups. All the hemodynamic parameters and other study parameters were similar at Min. 0. All the hemodynamic parameters such as heart rate, blood pressure and SpO2 were variable at different time intervals. Motor block level was significantly (p<0.05) lower in Group C than Group A and Group B from Min 50 to Min 90. The sedation score was observed to be nil in Group C. The post-op pain score became higher in Group C than Group A and Group B at subsequent time intervals. A 3 (10%) of the rescue agents was observed in Group C. Atropine (30%) and mephenteramine (10%) were common rescue agents in Group B. The bradycardia was observed in 30% patients of Group B and in 40% of Group A. Conclusions: On addition of dexmedetomidine as adjuvant to bupivacaine in epidural anesthesia provides better anesthesia and sedation than clonidine as adjuvant to bupivacaine or bupivacaine alone with mild hemodynamic changes which are easily manageable.